Perfil dos empreendedores e caracterização dos empreendimentos do município de São José de Mipibu - RN - Ambrosio, Mateus Lima (Universidade Federal Rural do Semi-Árido, 2019)
The present work deals with the characterization of the enterprises and entrepreneurs of the commerce of the Municipality of São José do Mipibu, located in the East region, in the State of Rio Grande do Norte. In this perspective, this work aims to identify the profile of the entrepreneurs and their enterprises in the city of São José do Mipibu, located in the East region, in the State of Rio Grande do Norte. Our research was guided by the following theoretical references: Brazilian Service of Support to Micro and Small Enterprises (SEBRAE), Dornelas, Marcondes, as well as the theoretical constructions of the research project (Code: PIF000402017) with the support of the Pro-Rectory of Research and Post-Graduation - PROPPG / UFERSA Angicos / RN, 2017, which explores the activities of the Municipalities of the State of Rio Grande do Norte. commercial and entrepreneurial activities of all regions of the State of Rio Grande do Norte. For the development of our research, we carried out a bibliographical and field research. As a data collection tool, we applied a questionnaire composed of 22 objective and subjective questions in 36 enterprises of the most varied market segments of the mentioned municipality. Our main objective was to collect the necessary information for the statistical survey, which were then represented in graphs, thus making a concrete analysis of the factors that hinder the development of the municipal enterprises. The survey was carried out from February 11 to February 14, 2019. Based on the analysis of the data, it was possible to diagnose the enterprises and to draw the profile of the entrepreneurs of the municipality in question, making a quantitative analysis of the data collected. With this, it is possible, in the future, to compare data, with the other cities of the State of Rio Grande do Norte, understanding, then, the economic scenario and, consequently, propose changes, aiming at a better perspective of development for the population of the region.
Monografia
Keywords: Empreendedorismo; Economia; Rio Grande do Norte; Entrepreneurship; Economy; Large northern river; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA